Collaborative Governance dalam Pengelolaan Sampah Kawasan Wisata Pantai Puruih Padang - Nur Aini; Nur Sakinah Mauliddia; Nurul Afri Dewi; Boni Saputra (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Waste management in coastal tourism areas is a complex issue that requires multi-stakeholder involvement. This study aims to analyze the implementation of collaborative governance in waste management in the Padang Beach Tourism Area, focusing on interaction patterns among actors, supporting factors, and existing challenges. A qualitative approach was employed through observation, in-depth interviews, and documentation, involving informants from the Environmental Agency as well as local communities and tourists. The findings reveal that waste management is still dominated by the Padang City Environmental Agency, indicating that collaborative governance has not been optimally implemented. Collaboration tends to be situational and emerges mainly during emergencies, such as the flash flood in November 2025, which significantly increased waste volume. Key challenges include low public awareness, limited facilities, weak inter- agency coordination, and the absence of structured collaboration mechanisms. This study recommends institutionalizing collaboration through multi-stakeholder forums, strengthening participatory regulations, improving infrastructure, and promoting continuous environmental education.